(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The rapid development of digital technology has led to the emergence of various forms of cybercrime, requiring adaptation within Indonesia’s criminal justice system. The complexity of digital offenses, particularly in relation to electronic evidence, places judges in a crucial position when interpreting the law and delivering fair decisions. This study aims to analyze judges’ considerations in digital-based criminal cases, identify factors influencing the assessment of electronic evidence, and evaluate the consistency of judicial decisions in similar cases. The research employs an empirical legal method with a qualitative socio-legal approach, combining the analysis of 12 court decisions with in-depth interviews involving five informants, including judges and legal practitioners. The findings reveal that judicial reasoning is not solely based on statutory provisions but is also shaped by technical understanding of digital evidence and the specific context of each case. Variations in decisions were identified in cases with similar characteristics, indicating the absence of standardized guidelines for evaluating electronic evidence. Additionally, judges’ experience and technological competence significantly influence decision-making quality. This study contributes theoretically by enriching empirical perspectives in criminal law and practically by offering insights for improving digital evidence assessment, emphasizing the need to integrate legal and technological understanding to ensure justice and legal certainty.